Correlation between the Jurisdiction of the Court of the EAEU and the Jurisdiction of International Judicial Institutions - ISKAKOVA, Zhanna Turkistanovna; KULIKPAYEVA, Mira Zhumagaziyevna; AKYLOV, Daulet Ospanuly; ZHANERKE, Zukay; KOSTYANAYA, Yuliya Sergeevna (Journal of Advanced Research in Law and Economics, 2018)
The article examines the complex problem of the concurrent (competing) jurisdiction of the Court of the Eurasian Economic Union (hereinafter – EAEU Court) with other international judicial institutions. This problem is getting more important in connection with the fragmentation of modern international law, the increasing number of judicial institutions which, when making decisions, adhere to their own legal positions, contradicting with the legal provisions previously established through court decisions of other integration associations in the identical disputes, which sometimes become crucial for states and international organizations. In our opinion, this phenomenon can become a destabilizing factor for the settlement of disputes arising among member states of the Eurasian Economic Union (hereinafter - EAEU) and subsequently for the successful functioning of the EAEU Court. Given the similarity of objects of legal regulation, member states of the EAEU have the right and opportunity to appeal to other international judicial institutions. This is due to the fact that the Treaty on the EAEU does not cover the issues of the priority of decisions of the Court and does not contain provisions in respect of dispute resolution mechanisms in cases where identical disputes can be simultaneously considered in other international judicial institutions. Unlike the member states, other states or other persons who apply to the court of the Union, have the right to apply for protection to the judicial authorities of other integration associations. The key aspect of our study is a comprehensive analysis of the essential characteristics that define the extent of the interference of the mutual influence of the EAEU Court with other international judicial institutions.